Remarkably bright creatures : a novel [compact disc, unabridged] - Van Pelt, Shelby (Harper Audio, 2022)
"After Tova Sullivan's husband died, she began working the night shift at the Sowell Bay Aquarium, mopping floors and tidying up. Keeping busy has always helped her cope, which she's been doing since her eighteen-year-old son, Erik, mysteriously vanished on a boat in Puget Sound over thirty years ago. Tova becomes acquainted with curmudgeonly Marcellus, a giant Pacific octopus living at the aquarium. Marcellus knows more than anyone can imagine but wouldn't dream of lifting one of his eight arms for his human captors, until he forms a remarkable friendship with Tova. Ever the detective, Marcellus deduces what happened the night Tova's son disappeared. And now Marcellus must use every trick his old invertebrate body can muster to unearth the truth for her before it's too late."--Container.